THE CORRELATION OF PERSONAL PROTECTIVE EQUIPMENT SOCIALIZATION TOWARD THE CHANGING OF OCCUPATIONAL SAFETY AND HEALTH BEHAVIOR OF MUSICAL INSTRUMENT CRAFTSMEN - Hamdani, Muhammad Zakwan; Rudyarti, Edwina; Phuspa, Sisca Mayang (Journal of Vocational Health Studies, 2018)
Background: Cultural conditions K3 in the industry Small Medium Enterprises (SME) craftsmen of traditional musical instruments is low only use 2 personal protective equipment that is protective mask and gloves. The condition can lead to accidents then exerts dissemination of the importance of personal protective equipment in order to minimize accidents. Purpose: This study aimed to determine the correlation between the socialisation of the importance of personal protective equipment (PPE) and the OSH behavior (knowledge and attitude toward the importance of PPE. Method: This was a quantitative research with Experimental approach. Craftsmen working population was taken as a respondent (24 workers). Data was taken by using a questionnaire and checklist. Related Data analysis used T-Test. Result: The results of this study scores showed the value of  p = 0.00 (p <0.05), which means that there were significant changes between the socialization of personal protective equipment and behavioral changes K3 workers craftsmen of traditional musical instruments industry in Paju District of Ponorogo. Further research is needed to study the behavior of K3 in the industry small medium enterprises on the other with the number of more samples and compare it to other industry small medium enterprises as well as a variable that has not been studied. Conclusion: Socialization of personal protective equipment can boost of knowledge and attitude for the workers to always use personal protective equipment in each work.